The paraventricular nucleus of the thalamus is recruited by both natural rewards and drugs of abuse: recent evidence of a pivotal role for orexin/hypocretin signaling in this thalamic nucleus in drug-seeking behavior - Matzeu, Alessandra; Zamora-Martinez, Eva R.; Martin-Fardon, Remi (Frontiers in Behavioral Neuroscience, 2014)
A major challenge for the successful treatment of drug addiction is the long-lasting susceptibility to relapse and multiple processes that have been implicated in the compulsion to resume drug intake during abstinence. Recently, the orexin/hypocretin (Orx/Hcrt) system has been shown to play a role in drug-seeking behavior. The Orx/Hcrt system regulates a wide range of physiological processes, including feeding, energy metabolism, and arousal. It has also been shown to be recruited by drugs of abuse. Orx/Hcrt neurons are predominantly located in the lateral hypothalamus that projects to the paraventricular nucleus of the thalamus (PVT), a region that has been identified as a “way-station” that processes information and then modulates the mesolimbic reward and extrahypothalamic stress systems. Although not thought to be part of the “drug addiction circuitry,” recent evidence indicates that the PVT is involved in the modulation of reward function in general and drug-directed behavior in particular. Evidence indicates a role for Orx/Hcrt transmission in the PVT in the modulation of reward function in general and drug-directed behavior in particular. One hypothesis is that following repeated drug exposure, the Orx/Hcrt system acquires a preferential role in mediating the effects of drugs vs. natural rewards. The present review discusses recent findings that suggest maladaptive recruitment of the PVT by drugs of abuse, specifically Orx/Hcrt-PVT neurotransmission.